Shade and nutrient-mediated phenotypic plasticity in the miracle plant Synsepalum dulcificum (Schumach. & Thonn.) Daniell - Tchokponhoué, Dèdéou A. (Sci Rep, 2019)
Phenotypic plasticity as a change of genotype expression in response to environmental heterogeneity varies in magnitude among crop species and can induce a shift in a plant’s phenology. In Synsepalum dulcificum, a West African orphan fruit tree, such phenological plasticity is not well understood. Here, we hypothesize that light stimulation and changes in organic nutrient availability would induce an accelerated transition in S. dulcificum from its juvenile to its reproductive phase. We grew 14-month-old seedlings of S. dulcificum under a range of nutrient regimes, both in shade and in full sunlight, and measured their survival, vegetative growth, biomass allocation, and transition to reproductive maturity. The results reveal that S. dulcificum responds favourably to both shading and nutrient application, with the shading exhibiting a stronger influence on the measured variables. The species’ morphological plasticity, particularly in terms of plant height and stem diameter, was found to exceed both its fitness and allocational plasticities. Under the conditions examined, we observed an accelerated transition to fruiting, at an age of only 24 months. The observed plasticity suggests S. dulcificum to be an intermediate shade-tolerant species. This finding expands our knowledge on the appropriate environmental conditions for the breeding and cultivation of this species.